Africa in the Year of Geopolitics - Siphamandla Zondi (African Journal of Political Science)
The year 2023 ended with the world on the precipice. The war in Gaza, a disproportionate Israeli military response to Hamas attack on a festival in Israel, is among the deadliest in decades. More than 20 000 people, mostly civilians including women and children had been killed in the Israeli bombing campaign to avenge the Hamas killing of 120 in October. Thousands have been displaced and injured